ANALISIS PENILAIAN PROPERTI RUMAH TINGGAL DI PERUMAHAN CITRALAND CITY SAMARINDA PADA KJPP. AKSA, NELSON & REKAN - Heriyanto Dan Dina Mustika (Prodi Ilmu Administrasi Negara, 2017)
Property Appraisal Analysis House Living In Citraland City Housing Samarinda At KJPP. Aksa, Nelson&Partners.Assessment is one service sector that can play an important role in shaping the economic value of assets and potential wealth. Value estimation is a realistic indication and can be sold at any given timeThe purpose of this study is to know and analyze the market value of residential property in Citraland City housing in Samarinda in 2016. Broadly speaking the problem is formulated as follows, whether the market value of residential property in Citraland City housing in Samarinda in 2016 has increased based on data approach Market and cost approach. The basic theory in this study is financial accounting that focuses on asset valuation. The hypothesis proposed is that the market value of residential property in Citraland City housing in Samarinda in 2016 has increased based on market data approach and cost approach.